Changing male perceptions of gender equality: Evidence from a randomised controlled trial study. (October 2022) - Nguyen, Cuong Viet; Tarp, Finn
Highlights: We examine whether self-exposure to gender documents can reduce gender bias of men in Vietnam. Commenting on gender-related laws does not reduce men's bias against women. Writing stories on gender has a strong effect on reducing existing prejudice against women. Writing stories also has a small and positive effect on doing housework. Changing men's behaviour in practice requires stronger, more sustained interventions. Abstract: In this study, we use a randomized control trial to examine whether asking Vietnamese men to reflect on gender equality can reduce their gender bias. We randomly selected two groups of married men in four rural provinces and asked the first group to make comments on gender-related laws and the second group to write stories about gender equality. We find that commenting on gender-related laws does not reduce men's bias against women, while writing stories has a strong effect on reducing prejudice against women. Writing stories increases the index of gender attitudes of men in the second group by 0.29 standard deviations. The assignment also has a small effect on their contribution to housework. Changing men's behaviour in practice requires stronger and more sustained interventions.